The emerging role of Hippo signaling pathway in regulating osteoclast formation. Issue 6 (15th January 2018) - Yang, Wanlei; Han, Weiqi; Qin, An; Wang, Ziyi; Xu, Jiake; Qian, Yu
Abstract : A delicate balance between osteoblastic bone formation and osteoclastic bone resorption is crucial for bone homeostasis. This process is regulated by the Hippo signaling pathway including key regulatory molecules RASSF2, NF2, MST1/2, SAV1, LATS1/2, MOB1, YAP, and TAZ. It is well established that the Hippo signaling pathway plays an important part in regulating osteoblast differentiation, but its role in osteoclast formation and activation remains poorly understood. In this review, we discuss the emerging role of Hippo‐signaling pathway in osteoclast formation and bone homeostasis. It is revealed that specific molecules of the Hippo‐signaling pathway take part in a stage specific regulation in pre‐osteoclast proliferation, osteoclast differentiation and osteoclast apoptosis and survival. Upon activation, MST and LAST, transcriptional co‐activators YAP and TAZ bind to the members of the TEA domain (TEAD) family transcription factors, and influence osteoclast differentiation via regulating the expression of downstream target genes such as connective tissue growth factor (CTGF/CCN2) and cysteine‐rich protein 61 (CYR61/CCN1). In addition, through interacting or cross talking with RANKL‐mediated signaling cascades including NF‐κB, MAPKs, AP1, and NFATc1, Hippo‐signaling molecules such as YAP/TAZ/TEAD complex, RASSF2, MST2, and Ajuba could also potentially modulate osteoclast differentiation and function. Elucidating the roles of the Hippo‐signaling pathway in osteoclast development and specific molecules involved is important for understanding the mechanism of bone homeostasis and diseases. Abstract : The Hippo‐pathway is involved in the cellular fate of osteoclasts, including pre‐osteoclast proliferation, osteoclast differentiation, and apoptosis. Hippo‐pathway interacts between osteoclast‐associated signaling pathways, including NF‐κB‐, MAPK‐, and calcium‐signaling pathways. Key molecular of Hippo‐pathway, RASSF2, Ajuba, MST2, YAP‐CTGF, and CYR61 modulate osteoclasts differentiation.